2015
DOI: 10.1109/lpt.2015.2470133
|View full text |Cite
|
Sign up to set email alerts
|

$4\times 4$ Silicon Optical Switches Based on Double-Ring-Assisted Mach–Zehnder Interferometers

Abstract: We present the experimental demonstration of a 4 × 4 silicon electro-optic (EO) switch fabric based on a Benes architecture. Double-ring-assisted Mach-Zehnder interferometers (DR-MZIs) are utilized as the basic switch elements. Silicon resistive microheaters and p-i-n diodes are embedded in both of the microrings of the DR-MZIs for low-loss thermooptic (TO) phase correction and high-speed switching operation, respectively. The TO tuning power dissipated to align all resonances is 22.37 mW. The maximum EO tunin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Using a similar principle, a 4 × 4 silicon integrated optical switch based on DR-MZIs has been further demonstrated. [63] The architecture is shown in A larger scale 16 × 16 silicon integrated optical switch based on DR-MZIs was further reported by Guo et al [70] The 2 × 2 DR-MZI basic element is also further improved compared with previous studies, and the basic structure is shown in (re-drawn from [63] ).…”
Section: Silicon Integrated Optical Switches Based On Mrr and Mzi Hyb...mentioning
confidence: 89%
See 1 more Smart Citation
“…Using a similar principle, a 4 × 4 silicon integrated optical switch based on DR-MZIs has been further demonstrated. [63] The architecture is shown in A larger scale 16 × 16 silicon integrated optical switch based on DR-MZIs was further reported by Guo et al [70] The 2 × 2 DR-MZI basic element is also further improved compared with previous studies, and the basic structure is shown in (re-drawn from [63] ).…”
Section: Silicon Integrated Optical Switches Based On Mrr and Mzi Hyb...mentioning
confidence: 89%
“…Using a similar principle, a 4 × 4 silicon integrated optical switch based on DR‐MZIs has been further demonstrated. [ 63 ] The architecture is shown in Figure , which is a rearrangeable non‐blocking switch with the 4 × 4 Benes switch fabric. There are a total of six switch elements organized in three stages, and each switch element is a 2×2 DR‐MZI switch described above.…”
Section: Silicon‐integrated Optical Switchesmentioning
confidence: 99%
“…Figure 1(a) depicts the schematic structure of the optical filter comprising two stages of DR-MZIs in a 2 × 2 lattice architecture [24], [25]. In order to make the filter reconfigurable, the originally fixed coupler is replaced by a tunable MZI-coupler as shown in Fig.…”
Section: Device Structure and Principlementioning
confidence: 99%
“…The Mach-Zehnder Interferometer (MZI) is one of the most commonly used optical instruments. The basic MZI structure consists of two waveguide arms, two Y-junctions, one of which serves as a beam splitter and the other as a beam combiner Several types of optical switch have been demonstrated over the past years using a variety of building blocks, including double-ring-assisted Mach-Zehnder interferometers (MZIs) [3,4], microring resonators (MRRs) [5], multimode interferometers (MMIs) [6], and MEMS-actuated adiabatic couplers [7] The primary advantage of MZI is its excellent resistance to temperature variations. But their large footprint results in a big footprint, when several MZIs are needed on a single chip loop-terminated asymmetric MZI (LT-aMZI) design based on the widespread SOI technology were proposed [8], enabling a smaller footprint and enhance the performance of the standard MZI in many applications.…”
Section: Introductionmentioning
confidence: 99%